Exercício isométrico versus isotônico no manejo da tendinopatia do manguito rotador - efeitos na dor, função, força e ativação muscular do ombro: ensaio clínico randomizado - Barros, Bianca Rodrigues da Silva (2024)
Introduction: Rotator cuff (RC) tendinopathy is a common shoulder disorder, and its conservative treatment mainly involves exercise programs, including strengthening and stretching of the periscapular and RC muscles, progressive loading exercises, and concentric and eccentric activation exercises. These interventions have been shown to improve shoulder pain and function. While isometric exercises have been extensively studied in the treatment of tendinopathies in the lower limbs, their application in RC tendinopathy requires further investigation. Objective: To compare the effects of isometric versus isotonic exercises on shoulder pain, function, shoulder muscle strength and activity in individuals with RC tendinopathy. Materials and methods: Forty-seven individuals, from both genders, with unilateral supraspinatus and/or infraspinatus tendinopathy were randomized into two groups: isometric (n=25; 42,4 ±11,6 years old; 26,3 ±3,2 kg/m2) and isotonic (n=22; 42,5 ±12,3 years old; 26,8 ±4,6 kg/m2). Assessments were conducted before and after the first treatment session, and after six weeks of intervention. Outcomes included pain, general shoulder function, isometric strength of shoulder elevation, external rotation (ER) and internal rotation (IR), and electromyographic activity of the middle deltoid, infraspinatus, serratus anterior, and lower trapezius muscles during strength tests. Both groups performed a stretching and strengthening protocol for the periscapular muscles and strengthening of the RC muscles according to the allocated group. Differences within and between groups were analyzed using Generalized Estimating Equations, adopting α < 5%. Results: After six weeks, both groups showed improvements in shoulder pain and function, IR muscle strength, and better infraspinatus muscle activation during the elevation strength test. The isometric group showed greater shoulder satisfaction, higher gains in ER muscle strength, and better infraspinatus activation in the ER strength test. Conclusion: Both isometric and isotonic exercises with progressive load are effective in reducing pain and improving function in individuals with RC tendinopathy. The isometric group showed higher shoulder satisfaction and superior strength in ER muscle strength, associated with increased infraspinatus muscle activation.